The Heat Exchange Coefficient of the Cooling Tube Under the Influence of the Tube Material and Cooling Water Parameters - Hong Zhang; Qiuliang Long; Fengqi Guo; Zhaolong Shen; Xu Chen; Ran Yu; Yonggang Wang (Buildings, 2025)
The traditional finite element method deals with the temperature field around the cooling tube due to the computational efficiency problems caused by grid division and the uncertainty of the convective heat transfer coefficient, resulting in inaccurate calculation results around the cooling tube. We conducted experiments to study the thermal stress and temperature gradient caused by various factors such as different materials of cooling pipes, pipe diameters, cooling water temperatures, and flow rates. The results showed that aluminum alloy pipes had the highest cooling efficiency but also produced a large temperature gradient. Pipe diameter had the most significant impact on cooling efficiency. Additionally, it is recommended that the cooling water flow velocity is not less than 0.6 m/s to achieve the best efficiency for the cooling pipe of any pipe diameter. The influence range of the cooling pipe on concrete could vary with pipe material, flow rate, and ambient factors. Our experimental results were compared with other heat transfer formulas (the Dittus–Boelter formula and the Yang Joo-Kyoung formula). According to the measured results, the formula is modified). The modified formula can estimate the heat transfer coefficient more accurately according to the flow rate and pipeline characteristics. Finally, the applicability of the formula is further verified by comparing the concrete on the bottom plate of a dam. The proposed heat transfer prediction model can estimate the heat transfer coefficient according to the flow rate and pipeline characteristics, The accuracy of the convection coefficient under different working conditions is improved by 10–25%. It is convenient to predict concrete temperature in practical engineering.